POLITENESS STRATEGIES IN RIA RICIS™ YOUTUBE ACCOUNT - Hari, Radhwa Khalisya; Natsir, Muhammad; Sinaga, Lidiman Sahat Martua (TRANSFORM: Journal of English Language Teaching and Learning, 2020)
This study was conducted by using descriptive qualitative method. This descriptive research attempted to decbribe the translation strategies which are used  in Ria Ricis™ YouTube account. The data of this research was the transcription of the videos in Ria Ricis™s Youtube account utterances, that was Indonesian. The researcher used a source of theories about politeness strategies by Yule™s theory to support the thesis. Some steps were undertaken during the data collection: the process of selecting, focusing on the important things, simplifying, abstracting and transforming the data that appear in transcription. The results showed that the most dominant type of politeness strategies is positive politeness strategy with 40 data (48%). The percentage of Bald On Record strategy was 24 data (29%). The percentage of Off Record strategy was 10 data (10%). The lowest percentage of politeness strategies is Negative Politeness with 9 data with 11%. The reason why the types of politeness strategies using in Ria Ricis™ YouTube account, instead of each politeness strategies has sub-strategies which explained those utterance contained politeness strategies.